Investigation of extraction and dehydration efficiency of granular coal sludges - Shkop, Andrii; Shestopalov, Oleksii; Ponomarova, Nataliia; Tseitlin, Musii; Romanchyk, Andrii (Технологічний центр, 2025)
The object of research is the process of extracting the solid phase and dewatering carboncontaining products of a coal enrichment plant in the technological chain of devices "drum screen – centrifuge". One of the most problematic areas of coal enrichment technology is the sludge waters of coal enrichment plants, which require high-quality cleaning and are promising for obtaining a fie coal fraction. This allows to reduce the load on radial thickeners, prevent coal losses and environmental pollution. During the study, an industrial experiment was used to determine the effiency of the module, which consisted of an Ecomash DS 511A-113 drum screen and an Ecomash SHS 511A-113 centrifuge. It was established that classes larger than 1.5 mm are advisable to capture and dewater by fitering on the developed drum screen to a moisture content of 15–22 % by fitration methods. Polydisperse sludge aftr removal of classes larger than 1.5 mm is effctively dehydrated in a centrifuge to a residual moisture of 19.7–33 %. The degree of sludge dehydration in a centrifuge is affcted by the fraction of the class content larger than 0.4 mm and the centrifuge feed capacity, which determine the formation time, compression and compactness of particle packing in the sludge. It has been established that when dewatering fie-dispersed sludge of fie classes with a particle size of less than 0.4 mm, the moisture content of the centrifuge sludge increases with increasing solid phase retention effiency. An increase in the fraction of fie-dispersed classes in the sludge, represented mainly by wet clay, leads to an increase in moisture content to 33 % and an increase in ash content to 83–85 %. An increase in the content of granular classes 0.4–1.5 mm to 30 % and above contributes to a decrease in sludge moisture content, other things being equal, due to the squeezing of moisture from the surface of fie particles that are squeezed by larger particles. The technological chain of the module, tested in industrial conditions, consisting of a fiter screen and a centrifuge, allows for the effctive extraction of the granular fraction of the sludge, capturing up to 87.4 % of the solid phase, leaving only fiely dispersed high-ash clay with a particle size of less than 40 microns in the centrate.
Keywords: polydisperse sludge; solid phase retention effiency; sludge dewatering; settling centrifuge; fitration; coal sludge purifiation